Color-change-resistant halogen flame-retardant PA66 material for electronic and electrical connectors and preparation method of color-change-resistant halogen flame-retardant PA66 material
By using a combination of zinc stannate and light stabilizers in PA66 materials, the color change problem caused by traditional flame retardants is solved, high flame retardant performance and long-term appearance stability are achieved, and the comprehensive performance of the material is improved.
Patent Information
- Application Number
- CN202510900730.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-09-02
AI Technical Summary
Traditional PA66 materials are prone to color change after adding halogen-antimonium trioxide flame retardant, which affects the product appearance and performance stability. The existing solutions have not effectively solved the compatibility problem.
Zinc stannate is used to replace antimony trioxide, and light stabilizers, antioxidants and dispersants are combined to control the ratio of halogen-based flame retardant and zinc stannate, and the flame retardant performance and appearance stability are improved, and the ultraviolet shielding effect is improved by using cyclodextrin composite ultraviolet absorbers.
It achieves excellent flame retardant performance and long-term appearance stability of PA66 material, and the flame retardant grade reaches UL94 V-0, significantly reducing color change, improving mechanical properties and weather resistance.
Smart Images

Figure BDA0005477137860000061 
Figure BDA0005477137860000062 
Figure BDA0005477137860000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors and a preparation method thereof. Background Art
[0002] At present, electronic and electrical connectors widely use PA66 as the polyamide material based on PA66. However, after adding halogen-antimony trioxide flame retardant, traditional PA66 is prone to color change, especially during extrusion and injection molding, which seriously affects the product appearance and performance stability.
[0003] Existing solutions often rely on increasing the flame retardant content or adding special stabilizers. While the former enhances the flame retardant effect, it also exacerbates the discoloration phenomenon. While the latter can alleviate the discoloration to a certain extent, the compatibility of these special stabilizers with the PA66 matrix has not been fundamentally resolved, which in turn affects the physical properties of the PA66 material. Therefore, with the electronics and electrical industry's increasing demand for safety and aesthetics, developing PA66 materials that have both excellent flame retardancy and long-term appearance stability has become a major challenge facing the industry. Summary of the Invention
[0004] In order to make the PA66 material have good flame retardant properties while maintaining a long-term stable appearance, the present application provides a color change resistant halogen flame retardant PA66 material for electronic and electrical connectors and a preparation method.
[0005] In the first aspect, the present application provides a color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors, which adopts the following technical solutions: A color change resistant halogen flame retardant PA66 material for electronic and electrical connectors comprises the following raw materials in percentage by weight: 12-20% of a halogen flame retardant, 2-4% of zinc stannate, 0.2-0.5% of a light stabilizer, 0.2-0.8% of an antioxidant, 0.1-0.3% of a dispersant, and the balance being nylon 66.
[0006] By adopting the above technical solution, the present application mainly solves the yellowing problem caused by the reaction between halogen flame retardants and antimony trioxide in the traditional solution by replacing antimony trioxide with zinc stannate. In addition, the flame retardant (such as brominated polystyrene) decomposes to generate HBr when heated, interrupting the combustion chain reaction; zinc stannate (ZnSnO3) acts as a metal oxide to catalyze dehydration and carbonization, reducing the generation of smoke and toxic gases; the ratio of halogen flame retardant and zinc stannate is limited, and the two work together to improve the flame retardant grade of PA66 material to UL94 V-0 grade, with excellent flame retardant properties; and the added dispersant (such as EBS) reduces the agglomeration of fillers (such as flame retardants, zinc stannate), improves the melt uniformity, and avoids the degradation of mechanical properties due to poor dispersion; on this basis, by adding light stabilizers and antioxidants, the color change during processing can be further significantly reduced. The stabilizer captures free radicals and the antioxidant decomposes peroxides. Their synergistic effect can further inhibit the photooxidative degradation of PA66, maintain long-term appearance stability in subsequent use, and improve the application potential of PA66.
[0007] Preferably, the light stabilizer is Tinuvin 770, and the antioxidant is Dovernox A-30.
[0008] By adopting the above technical solution, Tinuvin 770 has a higher molecular weight, which can reduce volatilization during high-temperature processing. Its compatibility with PA66 is better than that of low-molecular-weight HALS (such as Chimassorb 2020), and its precipitation risk is greatly reduced. When used in combination with the antioxidant Dovernox A-30 (amine antioxidant), the free radical capture efficiency can be improved, and the color change of the material after light aging can be greatly reduced. In addition, Dovernox A-30 has a metal passivation effect, which can passivate copper and iron ions in processing equipment, reduce catalytic oxidation, and delay surface corrosion of the material. The synergistic effect of Tinuvin 770 and Dovernox A-30 can extend the color change resistance of PA66 materials.
[0009] Preferably, the flame-retardant PA66 material further comprises a weathering synergist with a weight percentage of 0.1-0.5%, and the weathering synergist is a benzotriazole ultraviolet absorber.
[0010] By adopting the above technical solution, the benzotriazole UV absorber has a strong UV shielding ability, can absorb ultraviolet rays, reduce chain breakage caused by photodegradation, and improve the weather resistance of PA66; its UV shielding effect and Tinuvin 770's free radical capture effect synergize with each other to exert excellent color change resistance.
[0011] Preferably, the weathering synergist is a cyclodextrin composite UV absorber, and its preparation method is as follows: The ultraviolet absorber and cyclodextrin are ground in a mass ratio of 1:(1.5-3), and then dried to prepare a cyclodextrin composite ultraviolet absorber.
[0012] By adopting the above technical solution, the cyclodextrin cavity encapsulates the UV absorber, which can enhance the interfacial bonding with PA66 through hydrophobic interaction, greatly reducing the precipitation rate of the UV absorber and basically eliminating the white frost phenomenon on the surface of the PA66 material; and by encapsulating the UV absorber with cyclodextrin, the UV absorber can be slowly released, prolonging the UV shielding effect and extending the color change resistance of the PA66 material; in terms of process advantages: the grinding and drying method is simple and efficient, does not require complex equipment, and is suitable for industrial mass production.
[0013] Preferably, the cyclodextrin is succinyl-β-cyclodextrin.
[0014] By adopting the above technical solution, succinylation modification improves the lipophilicity of cyclodextrin, forms hydrogen bonds with the amide groups of PA66, and further improves the dispersion uniformity; and succinylation modification increases the carboxyl group in the molecular structure of cyclodextrin. During the processing, it can condense with the unreacted amino groups in the PA66 system, thereby further improving its compatibility and the integrity of the PA66 material.
[0015] Preferably, the weight percentage of the cyclodextrin composite ultraviolet absorber added is 0.3%.
[0016] By adopting the above technical solution, when too much cyclodextrin composite UV absorber is added, the mechanical properties of the PA66 material will be reduced. Therefore, when the weight percentage of the cyclodextrin composite UV absorber added is 0.3%, the comprehensive performance of the prepared PA66 material is stronger, which is a better addition amount.
[0017] Preferably, the viscosity of the nylon 66 is 2.4-2.7.
[0018] By adopting the above technical solution, the medium-viscosity PA66 melt has moderate fluidity, ensuring the uniform dispersion of fillers such as flame retardants and zinc stannate, while maintaining high crystallinity to meet the connector's plug-in life requirements.
[0019] In a second aspect, the present application provides a method for preparing a color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors, using the following technical solutions: A method for preparing a color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors, comprising the following steps: After drying the raw materials, the mixture is uniformly mixed at a rotation speed of 300-500 r / min, and then fed into a twin-screw extruder through a main feeding port. The mixture is extruded and granulated at a melting temperature of 270-290° C. to produce a color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors.
[0020] By adopting the above technical solution, the twin-screw extrusion temperature is controlled at 270-290℃, avoiding thermal oxidative degradation of PA66 and ensuring the mechanical properties of the material; the high-speed mixing and twin-screw shearing effect can ensure that fillers such as flame retardants and zinc stannate are evenly dispersed, avoiding performance degradation caused by local excessive concentration.
[0021] Preferably, the preparation method of the flame retardant PA66 material comprises the following steps: S1. Mixing raw materials except the halogen flame retardant and zinc stannate to prepare a mixture; S2. The mixed material is fed into a twin-screw extruder through a main feed port, and a halogen flame retardant and zinc stannate are added through a side feed port. The mixture is melt-extruded and granulated to obtain a color-discoloration-resistant halogen flame-retardant PA66 material for electronic and electrical connectors.
[0022] By adopting the above technical solution, halogen flame retardants and zinc stannate are sensitive to high temperatures, and side feeding can shorten their residence time in the barrel, reduce the generation of decomposition products, and reduce the release of hydrogen bromide; side feeding allows the flame retardant to be evenly distributed in the later stage of the melt, forming a denser carbonized layer, improving flame retardant properties, reducing local overheating of the flame retardant and the matrix resin, reducing the risk of degradation, and at the same time improving the mechanical properties of the material.
[0023] In summary, this application includes at least one of the following beneficial technical effects: 1. This application primarily addresses the yellowing problem caused by the reaction between halogenated flame retardants and antimony trioxide in traditional solutions by replacing antimony trioxide with zinc stannate. Furthermore, the flame retardant (e.g., brominated polystyrene) decomposes upon heating to produce HBr, interrupting the combustion chain reaction. Zinc stannate (ZnSnO3), as a metal oxide, catalyzes dehydration and carbonization, reducing the generation of smoke and toxic gases. The ratio of the halogenated flame retardant to zinc stannate is defined, and the synergistic effect of the two enhances the flame retardancy of the PA66 material to UL94 V-0, demonstrating excellent flame retardancy. Furthermore, the addition of a dispersant (e.g., EBS) reduces agglomeration of fillers (e.g., flame retardant and zinc stannate), improves melt uniformity, and avoids degradation of mechanical properties due to poor dispersion. Furthermore, the addition of a light stabilizer and an antioxidant further significantly reduces color change during processing. The stabilizer captures free radicals, and the antioxidant decomposes peroxides. Their synergistic effect further inhibits the photo-oxidative degradation of PA66, maintaining long-term appearance stability during subsequent use and enhancing the application potential of PA66.
[0024] 2. The present invention has excellent color change resistance, flame retardancy and mechanical properties; its L value is between 84.40-89.27, the a value is between (-0.34)-(-0.22), and the b value can reach between 8.10-8.66. Moreover, after 500 hours of xenon lamp irradiation, the changes in various parameters are relatively low, indicating that its color change resistance has good stability; on this basis, its flame retardancy reaches UL 94V-0 level; the tensile strength is between 64.6-65.7MPa, the flexural strength is between 111-116MPa, and the notched impact strength reaches 3.8-4.5kJ / m 2 . DETAILED DESCRIPTION
[0025] The following is a further detailed description of this application in conjunction with the specific content.
[0026] raw material The raw materials used in the examples of this application are all commercially available products. Among them, nylon 66, brand Shenzhen DuPont; brominated polystyrene, model BPS-7010, purchased from Shandong Brothers; zinc stannate, purchased from Yunnan Tin Industry; antioxidant, Dovernox A-30, brand Dover, USA; succinyl-β-cyclodextrin, purchased from Shaanxi Lantai Bioengineering Co., Ltd.; UV absorber, Tinuvin 326, brand BASF; light stabilizer, Tinuvin 770, brand BASF; dispersant, EBS, model Ceridust 3615, brand BASF. Example
[0027] Example 1 A color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors, the raw materials and amounts of which are shown in Table 1, and the preparation method thereof is as follows: The raw materials were dried according to the ratios in Table 1 and mixed in a high-speed mixer at a rotation speed of 400 r / min. After uniform mixing, the mixture was fed into a twin-screw extruder through a main feed port and extruded into granules at a melt temperature of 280°C to produce a color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors.
[0028] Table 1 Raw materials and amounts of raw materials used in Example 1 (kg) Nylon 66 (viscosity 2.4) Replenish to 100 Brominated polystyrene 16 zinc stannate 3 Light stabilizers 0.35 antioxidants 0.5 dispersants 0.3 Example 2 A color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors, which differs from Example 1 in that its preparation method is as follows: S1. After drying the raw materials according to the ratio in Table 1, the raw materials except brominated polystyrene and zinc stannate were mixed in a high-speed mixer at a speed of 400 r / min to obtain a mixture; S2. The mixed material is fed into a twin-screw extruder through a main feed port, brominated polystyrene and zinc stannate are added through a side feed port, and the mixture is extruded and granulated at a melt temperature of 280° C. to produce a color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors.
[0029] Example 3 A color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors differs from Example 2 in that the raw materials further include 0.1 kg of a weathering synergist, which is a UV absorber, and the UV absorber is Tinuvin 326. The remaining steps are the same as those in Example 2.
[0030] Example 4 A color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors differs from Example 3 in that its weathering synergist is a cyclodextrin composite UV absorber, which is prepared by the following preparation method: The ultraviolet absorber and succinyl-β-cyclodextrin were ground in a mass ratio of 1:2 for 30 minutes, and then dried at 70° C. to prepare a weathering synergist.
[0031] Example 5 A color-discoloration-resistant halogen flame-retardant PA66 material for electronic and electrical connectors is different from Example 4 in that the amount of weathering synergist added is 0.3 kg, and the remaining steps are the same as Example 4.
[0032] Example 6 A color-discoloration-resistant halogen flame-retardant PA66 material for electronic and electrical connectors is different from Example 4 in that the amount of weathering synergist added is 0.5 kg, and the remaining steps are the same as Example 4.
[0033] Example 7 A color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors differs from Example 4 in that, during the preparation of its weathering synergist, succinyl-β-cyclodextrin is replaced with β-cyclodextrin of equal mass, and the remaining steps are the same as those in Example 4.
[0034] Comparative Example Comparative Example 1 A color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors is different from Example 1 in that zinc stannate is replaced with antimony trioxide of equal mass, and the remaining steps are the same as those in Example 1.
[0035] Comparative Example 2 A color-discoloration-resistant halogen flame-retardant PA66 material for electronic and electrical connectors is different from Example 1 in that the antioxidant is antioxidant 1098, and the remaining steps are the same as Example 1.
[0036] Performance testing Detection method / test method Flame-retardant PA66 materials were prepared according to the preparation methods of Examples 1-7 and Comparative Examples 1-2, and then tested according to the following test methods. The test results are shown in Tables 2 and 3.
[0037] The color change tendency is mainly blackening (low L value) and yellowing (high b value). The a value is mainly used to evaluate the performance of the red-green phase. The L value, b value and a value of the color change are tested by a colorimeter. Then, after each sample is irradiated with a xenon lamp for 500 hours, it is tested again by the colorimeter. The test data are shown in Table 2.
[0038] Tensile strength: tested by the test method in ISO 527; Bending strength: tested by the test method in ISO 178; Notched impact strength: tested by the dropping test method in ISO 179; Flame retardant grade: Passed UL 94:2017: Tests the self-extinguishing and dripping ignition properties of vertically burning materials and is rated V-0 / V-1 / V-2.
[0039] Table 2 Background color detection data of Examples 1-7 and Comparative Examples 1-2 Table 3 Mechanical properties test data of Examples 1-7 and Comparative Examples 1-2 It can be seen from the test data of Examples 1-7 and Comparative Examples 1-2, as well as Tables 2-3, that the present application has excellent color change resistance, flame retardancy and mechanical properties; its L value is between 84.40-89.27, its a value is between (-0.34)-(-0.22), and its b value can reach between 8.10-8.66. Moreover, after 500 hours of xenon lamp irradiation, its various parameters change less, indicating that its color change resistance has good stability; on this basis, its flame retardancy reaches UL 94V-0 level; its tensile strength is between 64.6-65.7MPa, its flexural strength is between 111-116MPa, and its notched impact strength reaches 3.8-4.5kJ / m 2 .
[0040] This application primarily addresses the yellowing problem caused by the reaction between halogenated flame retardants and antimony trioxide in traditional solutions by replacing antimony trioxide with zinc stannate. Furthermore, the flame retardant (e.g., brominated polystyrene) decomposes upon heating to produce HBr, interrupting the combustion chain reaction. Zinc stannate (ZnSnO3), as a metal oxide, catalyzes dehydration and carbonization, reducing the generation of smoke and toxic gases. The ratio of the halogenated flame retardant to zinc stannate is defined, and the two synergistically elevate the flame retardancy of the PA66 material to UL94V-0, exhibiting excellent flame retardancy. Furthermore, the addition of a dispersant (e.g., EBS) reduces agglomeration of fillers (e.g., flame retardant and zinc stannate), improves melt uniformity, and avoids degradation of mechanical properties due to poor dispersion. Furthermore, the addition of a light stabilizer and an antioxidant can further significantly reduce color change during processing. The stabilizer captures free radicals, and the antioxidant decomposes peroxides. Their synergistic effect further inhibits the photo-oxidative degradation of PA66, maintaining long-term appearance stability during subsequent use and enhancing the application potential of PA66. This can be verified by the test data of Example 1 and Comparative Example 2.
[0041] The test data from Examples 1 and 2 show that halogen flame retardants and zinc stannate are sensitive to high temperatures. Side feeding can shorten their residence time in the barrel, reduce the formation of decomposition products, and lower the release of hydrogen bromide. Side feeding evenly distributes the flame retardant in the later stages of the melt, forming a denser carbonized layer, improving flame retardancy, reducing local overheating of the flame retardant and the matrix resin, lowering the risk of degradation, and simultaneously improving the material's resistance to discoloration and mechanical properties. Combining Examples 3-4 with Example 7, benzotriazole UV absorbers have strong UV shielding capabilities, absorbing UV rays and reducing chain scission caused by photodegradation, thereby improving the weather resistance of PA66. Their UV shielding effect synergizes with the free radical capture effect of Tinuvin 770 to achieve excellent discoloration resistance. Succinylation modification increases the lipophilicity of cyclodextrin, forming hydrogen bonds with the amide groups of PA66, and further improving the dispersion uniformity. In addition, succinylation modification increases the carboxyl groups in the molecular structure of cyclodextrin, which can condense with the unreacted amino groups in the PA66 system during processing, thereby further improving its compatibility and the integrity of the PA66 material.
[0042] It can be seen from the test data of Examples 4-6 that when too much cyclodextrin composite UV absorber is added, the mechanical properties of the PA66 material will be reduced. Therefore, when the weight percentage of the cyclodextrin composite UV absorber added is 0.3%, the comprehensive performance of the prepared PA66 material is stronger, which is a better addition amount.
[0043] This specific embodiment is merely an explanation of the present invention and is not intended to limit the present invention. After reading this specification, those skilled in the art may make non-creative modifications to this embodiment as needed. However, as long as such modifications are within the scope of the claims of the present invention, they are protected by patent law.
Claims
1. A color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors, characterized by: The invention comprises the following raw materials in percentage by weight: 12-20% of a halogen flame retardant, 2-4% of zinc stannate, 0.2-0.5% of a light stabilizer, 0.2-0.8% of an antioxidant, 0.1-0.3% of a dispersant, and the balance being nylon 66.
2. The color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors according to claim 1, characterized in that: The light stabilizer is Tinuvin 770, and the antioxidant is Dovernox A-30.
3. The color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors according to claim 1, characterized in that: The flame retardant PA66 material further includes a weathering synergist with a weight percentage of 0.1-0.5%, and the weathering synergist is a benzotriazole ultraviolet absorber.
4. The color-discoloration-resistant, halogen-flame-retardant PA66 material for electronic and electrical connectors according to claim 3, characterized in that: The weathering synergist is a cyclodextrin composite UV absorber, and its preparation method is as follows: The ultraviolet absorber and cyclodextrin are ground in a mass ratio of 1:(1.5-3), and then dried to prepare a cyclodextrin composite ultraviolet absorber.
5. The color change resistant halogen flame retardant PA66 material for electronic and electrical connectors according to claim 4, characterized in that: The cyclodextrin is succinyl-β-cyclodextrin.
6. The color change resistant halogen flame retardant PA66 material for electronic and electrical connectors according to claim 5, characterized in that: The weight percentage of the cyclodextrin composite ultraviolet absorber added is 0.3%.
7. The color change resistant halogen flame retardant PA66 material for electronic and electrical connectors according to claim 1, characterized in that: The viscosity of the nylon 66 is 2.4-2.
7.
8. A method for preparing the color change resistant halogen flame retardant PA66 material for electronic and electrical connectors according to any one of claims 1 to 7, characterized in that: It includes the following steps: After drying the raw materials, the mixture is uniformly mixed at a rotation speed of 300-500 r / min, and then fed into a twin-screw extruder through a main feeding port. The mixture is extruded and granulated at a melting temperature of 270-290° C. to produce a color-discoloration-resistant halogen-flame-retardant PA66 material for electronic and electrical connectors.
9. The method for preparing the color change resistant halogen flame retardant PA66 material for electronic and electrical connectors according to claim 8, characterized in that: The preparation method of the flame retardant PA66 material comprises the following steps: S1. Mixing raw materials except the halogen flame retardant and zinc stannate to prepare a mixture; S2. The mixed material is fed into a twin-screw extruder through a main feed port, and a halogen flame retardant and zinc stannate are added through a side feed port. The mixture is melt-extruded and granulated to obtain a color-discoloration-resistant halogen flame-retardant PA66 material for electronic and electrical connectors.